Transhumanisme Dan Tantangannya Dalam Kekristenan: Antara Teknologi Dan Kehendak Allah - Sinaga, Roy Mazmur; Sirait, Hikman; Pandie, Remegises Danial Yohanis Pandie (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2025)
Transhumanism is a philosophical and cultural movement that focuses primarily on transcending the biological limitations of humans through technological advancement. In the Christian context, transhumanism poses a number of theological, moral, and spiritual challenges. Many Christian thinkers are concerned that transhumanism could undermine the traditional understanding of humans as creatures created in the image of God, and threaten the moral and ethical values ​​that underlie Christian teaching. Drawing on figures such as Ray Kurzweil and Nick Bostrom, as well as a review of recent literature, this article seeks to answer the fundamental question: how can Christianity respond to attempts to replace dependence on God with dependence on technology? It also offers insights into how the church can play a critical role in guiding people in the face of technological advancement. The result is that the church needs to re-teach the values ​​of the Imago Dei, the church needs to become a place for discussion of God's will for humanity as a central theme in Christian theology that includes understandings of creation, purpose of life, salvation, the end of time and human relationship with God.